The perception of fake news in higher education students: A bibliographic review - Ramos Ruiz, Ismael (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Fake news appears in digital spaces whether in written or audiovisual format. Its appearance of journalistic information can mislead recipients. Therefore, it is very important to know how to recognize them and protect oneself from their effects. Thus, the education system, particularly university education, can play a key role in this task. The aim of this bibliographic review is to identify the papers dealt with the perception of university students about fake news. In particular, this study focus on the different research methods used to analyze the perception of students.